If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -4 + -3x + -3 = 3 Reorder the terms: -4 + -3 + 6x + -3x = 3 Combine like terms: -4 + -3 = -7 -7 + 6x + -3x = 3 Combine like terms: 6x + -3x = 3x -7 + 3x = 3 Solving -7 + 3x = 3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 3x = 3 + 7 Combine like terms: -7 + 7 = 0 0 + 3x = 3 + 7 3x = 3 + 7 Combine like terms: 3 + 7 = 10 3x = 10 Divide each side by '3'. x = 3.333333333 Simplifying x = 3.333333333
| X^2-5x-y=0 | | 3h-2=35 | | 3(X/7)=24 | | (2x+4)(5x+5)= | | 2(3x-2)-3(x+1)=3 | | (C-2)(C-5)= | | y[n]-0.5*y[n-2]=0 | | 24/2=4/2x | | 44=2(4+3x)+2(4+5x) | | 2x(x+e)=3e(x+e) | | 162=2xsquared | | 4s^2+19=12s | | x/y=2.727272 | | 10x-x^2=5 | | 10x-y^2=5 | | 3+4x-10=17 | | N(14+6)=22 | | (a+1)(a*2+3a+1)= | | x^2-61.28x=2000 | | 15+3y=51-y-y-y | | 16-7m=30 | | 5-3y+5y=-8+6+9y | | -(x-1)=x-5 | | 64-32y=55-35y | | 27=5-2x | | 7+91x=52x+3 | | -2(x-5)=10-3x | | 6x-3x(x-1)=21 | | 2x^2+2y-1=0 | | 2cosx+4sinx=3 | | 16x-5y=125 | | 2y-4=29 |